Maternal and perinatal Health Research Collaboration, India (MaatHRI): methodology for establishing a hospital-based research platform in a low and middle income country setting - Nair, M; Bezbaruah, B; Bora, AK; Bora, K; Chhabra, S; Choudhury, SS; Choudhury, A; Deka, D; Deka, G; Ismavel, VA; Kakoty, SD; Koshy, RM; et al. (F1000Research, 2020)
Background: Maternal and perinatal Health Research collaboration, India (MaatHRI) is a research platform that aims to improve evidence-based pregnancy care and outcomes for mothers and babies in India, a country with the second highest burden of maternal and perinatal deaths. The objective of this paper is to describe the methods used to establish and standardise the platform and the results of the process.